El rol actual de la mujer Shuar y la educación Estudio de caso en el Centro de Formación Artesanal Nankamaku - Mejeant, Lucía (1996)
Introduction. Fiscomisional craft training center. Nalamaku. Location and history. Arrival of the Salesian missionaries. Formal education of the Shuar woman at boarding school. Missionaries in education. Gender and culture. Gender and education. Field research. Conclusions. Recommendations. Bibliography. Interviews. Annexes. Questionnaires. Photos.